2000
DOI: 10.1128/iai.68.6.3108-3115.2000
|View full text |Cite
|
Sign up to set email alerts
|

EnterohemorrhagicEscherichia coliInduces Apoptosis Which Augments Bacterial Binding and Phosphatidylethanolamine Exposure on the Plasma Membrane Outer Leaflet

Abstract: Enterohemorrhagic Escherichia coli (EHEC) is a gastrointestinal pathogen that causes watery diarrhea and hemorrhagic colitis and can lead to serious and even fatal complications such as hemolytic uremic syndrome. We investigated the ability of EHEC to kill host cells using three human epithelial cell lines. Analysis of phosphatidylserine expression, internucleosomal cleavage of host cell DNA and morphological changes detected by electron microscopy changes revealed evidence of apoptotic cell death. The rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 50 publications
(52 reference statements)
1
33
0
2
Order By: Relevance
“…Studies from Barnett-Foster et al and Jones et al demonstrated that Shiga toxins may play a role in inducing apoptosis in some intestinal epithelial cell lines (3,17). Shiga toxins have previously been observed to mediate intestinal damage by cellular apoptosis in a rabbit ileal loop model (18).…”
Section: Shiga Toxins Made By Shiga Toxin-producingmentioning
confidence: 99%
“…Studies from Barnett-Foster et al and Jones et al demonstrated that Shiga toxins may play a role in inducing apoptosis in some intestinal epithelial cell lines (3,17). Shiga toxins have previously been observed to mediate intestinal damage by cellular apoptosis in a rabbit ileal loop model (18).…”
Section: Shiga Toxins Made By Shiga Toxin-producingmentioning
confidence: 99%
“…Like many enteric pathogens EPEC and EHEC are able to induce apoptosis upon infection. 180,181 However, apoptosis induction needs to be modulated in order to maintain an infective niche within a host, by balancing pro and anti-apoptotic effectors (Fig. 5E).…”
mentioning
confidence: 99%
“…Epithelial cell death is a well-known consequence of EPEC infection (32)(33)(34)(35)(36)(37). Furthermore, in human EPEC infection cases, pathological evidence of intestinal damage has been found (17,18,38).…”
Section: Discussionmentioning
confidence: 99%